Derby girl - Cross, Shauna (Henry Holt and Company, 2007)
When sixteen-year-old rebel Bliss Cavendar, who is miserable living in a small Texas town with her beauty pageant-obsessed mother, secretly joins a roller derby team under the name "Babe Ruthless," her life gets better, although infinitely more confusing.
Keywords: Roller derbies -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Roller derbies -- Fiction; Identity -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Texas -- Juvenile fiction; Texas -- Fiction; Jugendbuch